The archaeology of the Bible - Hoffmeier, James K. (Lion, 2008)
Taking the reader on a fascinating journey around the archaeological remains of the Ancient Near East, The Archaeology of the Bible provides a review of Bible history and examines the role of archaeology in understanding the biblical text. Beginning with Genesis and the origins of the world, it follows the Bible narrative right through to the early churches of Revelation. Beautifully illustrated, the book is interspersed with stories from the author's own experience as an archaeologist, bringing the thrill of archaeological discovery vividly to life. It is an ideal introduction for anyone interested in learning more about the societies and events of the Ancient Near East and how they affect our understanding of the Bible.